2019
DOI: 10.1103/physrevd.100.125020
|View full text |Cite
|
Sign up to set email alerts
|

History state formalism for scalar particles

Abstract: We present a covariant quantum formalism for scalar particles based on an enlarged Hilbert space. The particular physical theory can be introduced through a timeless Wheeler DeWitt-like equation, whose projection onto four-dimensional coordinates leads to the Klein Gordon equation. The standard quantum mechanical product in the enlarged space, which is invariant and positive definite, implies the usual Klein Gordon product when applied to its eigenstates. Moreover, the standard three-dimensional invariant meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…On the one hand, this will permit us to prove full equivalence of the so-obtained relational quantum dynamics with the manifestly gauge-invariant formulation in terms of relational Dirac observables on H phys of Dynamics (i). As an aside, this will also resolve the normalization issue of physical states appearing in Diaz et al [50], where the kinematical rather than physical inner product was used to normalize physical states, thus yielding a divergence (when used for equal mass states). On the other hand, the covariant clock POVM will allow us, in section 6, to address the observation by Kuchař [1] that using the Minkowski time observable leads to incorrect localization probabilities for relativistic particles in the Page-Wootters formalism.…”
Section: Dynamics (Ii): the Page-wootters Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, this will permit us to prove full equivalence of the so-obtained relational quantum dynamics with the manifestly gauge-invariant formulation in terms of relational Dirac observables on H phys of Dynamics (i). As an aside, this will also resolve the normalization issue of physical states appearing in Diaz et al [50], where the kinematical rather than physical inner product was used to normalize physical states, thus yielding a divergence (when used for equal mass states). On the other hand, the covariant clock POVM will allow us, in section 6, to address the observation by Kuchař [1] that using the Minkowski time observable leads to incorrect localization probabilities for relativistic particles in the Page-Wootters formalism.…”
Section: Dynamics (Ii): the Page-wootters Formalismmentioning
confidence: 99%
“…(i) a Dirac quantization scheme, wherein relational observables are constructed that encode correlations between evolving and clock degrees of freedom [1,2,4,, (ii) the Page-Wootters formalism, which defines a relational dynamics in terms of conditional probabilities for clock and evolving degrees of freedom [7,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], and (iii) classical or quantum deparametrizations, which result in a reduced quantum theory that only treats the evolving degrees of freedom as quantum [1,2,7,10,30,31,[58][59][60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps a PaW formulation of spacetime may represent a first step towards removing this asymmetry. This might help to develop relativistic generalizations of the PaW formalism, see also [31,32,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Back in 1983 Don N. Page and William K. Wootters (PaW) suggested that time can be an emergent property of entanglement between subsystems in a globally static Universe [4,5], a proposal that has recently attracted much attention [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] as a viable route for a new description of space-time, including a new perspective for merging quantum clocks and gravity [24,25] (see Appendix A for a brief summary of PaW).…”
Section: Introductionmentioning
confidence: 99%